Evaluation of long term performance for initial public offerings using Market Adjusted Cumulative Abnormal Returns (MACAR): a case study of Islamic finance in Malaysia - Abu Bakar, Nashirah; Rosbi, Sofian; Uzaki, Kiyotaka (2019)
The main objective of this paper is to evaluate the long term performance of initial public offerings for sharia compliant companies listed on the Malaysia Stock Exchange. The number of selected companies is 17 that issued initial public offerings (IPO) in the year of 2014 and 2015. Data for analysis in this study are collected from Thomson Reuters Datastream. The daily stock price is collected and then averaged to attained monthly share price. Next, this study using market adjusted cumulative abnormal returns (MACAR) to evaluate the performance of initial public offerings. In the same time, this study implemented the Shapiro-Wilk normality test to check the normality of data distribution. The result shows the MACAR value is -46.0024 % for 17 sharia-compliant companies. The negative value indicates the companies performed less than the benchmarked market namely Kuala Lumpur Stock Exchange (KLSE). Therefore, the findings show the market performed better than companies that issued IPO. The importance of this finding is it will help investors to make a better decision in developing their investment portfolio in gaining better profit and reducing the loss. In addition, the findings also will help the financial analyst to understand the dynamic behavior of the financial environment in Malaysia Stock Exchange.